N-Heterocyclic carbene-catalyzed enantioselective synthesis of spiro-glutarimides via alpha,beta-unsaturated acylazoliums - Mondal, Santigopal; Ghosh, Arghya; Mukherjee, Subrata; Biju, Akkattu T. (Organic Letters, 2018)
NHC-catalyzed enantioselective [3 + 3] spiro-annulation of alpha,beta-unsaturated aldehydes with cyclic beta-ketoamides allowing the preparation of synthetically and biologically important spiro-glutarimide derivatives has been reported. The interception of the ketoamides with catalytically generated chiral alpha,beta-unsaturated acylazoliums proceeds in a Michael addition-intramolecular amidation pathway to deliver the spirocyclic products with good yield, diastereoselectivity, and enantioselectivity.